Lipocalin 2 deficiency impacts angiogenesis after ischemia in vivo and in vitro - L Zhang; Z Aref; H A B Peters; M R de Vries; A Y Nossent; P H A Quax (Vascular Biology)
Therapeutic neovascularization is a promising therapy option for patients with peripheral arterial disease. We followed in time the gene expression after induction of hind limb ischemia in mice with different patterns of blood flow restoration and identified lipocalin 2 (LCN2) as a strongly upregulated factor whose role in neovascularization deserves further investigation. In this study, we investigated the role of LCN2 in angiogenesis using the hind limb ischemia (HLI) model, ex vivo angiogenic aortic ring assay, and by assessing the pre-existing collaterals in the pial circulation in both Lcn2−/− mice and wild-type (WT) mice. This demonstrated an upregulated mRNA expression of Lcn2 after HLI and reduced post-ischemic angiogenesis in Lcn2−/− compared to WT mice. In the aortic ring assay, angiogenic sprouting was decreased in Lcn2−/− compared to WT mice. The blood flow recovery and arteriogenesis after HLI and preexisting collateral density in the pial circulation were similar in Lcn2−/− and WT mice. In vitro, siRNA-mediated LCN2 knockdown impaired HMVEC migration and tube formation. These results show that LCN2 is a potential pro-angiogenic factor and that LCN2 downregulation has a negative effect on angiogenesis in vivo and in vitro.